Case of Cephalic Presentation of a Foetus in a Harbour Porpoise Phocoena phocoena (Cetacea, Phocoenidae), with Notes on Other Aquatic Mammals - Gol’din, P.E. (Вестник зоологии, 2011)
A stranded harbour porpoise pregnant with a near-term foetus in cephalic (head) presentation was found. It is the first time when cephalic presentation, now recorded in three odontocete families, is reported for phocoenids. It proved to occur rarely, yet to be more widespread for aquatic mammals than could be expected. Обнаружена выброшенная на берег морская свинья, беременная предродовым плодом в головном предлежании. Головное предлежание впервые отмечено у морских свиней и теперь известно у представителей трех семейств зубатых китов. Это явление редко встречается у водных млекопитающих, однако распространено шире, чем предполагалось.